Transpiração e eficiência de uso da água em plantios puros e mistos de eucalyptus grandis e acacia mangium - Deus Júnior, José Carlos de [UNESP] (2014)
Mixed-species plantations with nitrogen-fixing species such as Acacia mangium have been proposed as an alternative to eucalypt monocultures in order to enhance soil nutrient availability and wood production. However, it is unclear if these changes in wood production are associated to equivalent changes in water-use. Thus this study aimed to compare the transpiration and water use efficiency in pure and mixed-species stands of Eucalyptus grandis Hill ex Maiden and Acacia mangium Wild in Brazil. Transpiration and growth were measured at mid rotation, between ages 2.8 and 3.8 years, in monocultures of E. grandis (100E), A. mangium (100A) and in mixtures with 50% of each species (50A50E) at the same total stocking density, in a randomized block experiment. Allometric relationships between stemwood dry matter (DM) and leaf area were established at age 3.2 years sampling destructively 10 trees per species in each treatment. Granier sap flow probes were used to estimate over one year the transpiration for 10-15 stems per species covering the range of basal areas in each treatment. A regression was established daily for each species between tree transpiration and tree diameter at breast height (DBH) in each treatment and applied to the DBH of all the trees in the experiment (interpolated linearly between the census made every 3 months). Leaf area index (LAI) at 3 years of age was 5.5, 4.1 and 5.1 in 100A, 100E and 50A50E, respectively. The aboveground biomass increment production at mid rotation was higher in E. grandis monoculture (77.7 Mg ha-1) than in A. mangium monoculture (54.2 Mg ha-1) and intermediate in mixed-species stands (68.2 Mg ha-1). The annual transpiration was also higher in 100E (1180 mm), than in 100A (906 mm) and in 50A50E (996 mm; 725 mm and 271 mm for eucalypts and acacias, respectively). Water use efficiency was 2.2 kg DM m-3 in E. grandis monoculture and in mixed plantation and was 10%